Cognitive Function In Old Age - Turgunova Aziza Tashpulatovna (Euro Asian Journal Publishing, 2025)
This article discusses the effectiveness of developing cognitive activity in the elderly, measures and methods aimed at preserving and improving a person's mental and intellectual potential, and the fact that this process, first of all, includes supporting and developing cognitive functions, such as memory, attention, thinking, and problem-solving skills, in old age
Keywords: older generation; cognitive activity; development